Detection and evolution of disaster sources in high slopes of open-pit mines based on time-lapse high-density electricity method - Sen, Kang; Zihao, Zhao (Frontiers in Earth Science, 2023)
High and steep slopes are common in open pit mines used for ore production, and ensuring the stability of these slopes is crucial for safeguarding people's lives, property, and social welfare. To achieve this, it is essential to control the evolution of disaster sources within slopes and refine their distribution. This requires a detailed understanding of the evolutionary characteristics of these sources. This paper presents a novel approach to identify the evolution of hazard sources within slopes by utilizing the derivative of normalized inversion data versus time as a characteristic feature. The raw apparent resistivity data collected at different times are subjected to smoothing and wavelet denoising algorithms to reduce noise, and geological constraints are applied to the collected data using the parametric region method. The least squares method is adopted for independent inversion, and the inversion results are standardized. Subsequently, the standardized inversion results are employed to derive the derivative of resistivity versus time equation, which highlights the evolution of the hazard source through the derivative of the normalized inversion resistivity versus time interval in the same location area. The evolution of hazard sources within the slope is analyzed using a large open pit rocky slope as a case study. The results indicate that the smoothing and wavelet threshold denoising algorithms effectively suppress the noise generated by the acquisition equipment and the electromagnetic interference noise in the environment. The parametric area method reduces the impact of different detection conditions by imposing geological constraints on the detection area, thereby highlighting the spatial and temporal evolution characteristics. The hazard sources within the slope have evolved to varying degrees, with the derivatives of resistivity and time interval in the areas of significant evolution mostly greater than 0.1, and concentrated in the shallow part, where water erosion and blasting vibration have significant contributions. The areas with lithological stability have not undergone significant changes, while the original hazard source areas have evolved to different extents, which can be distinguished based on the size and sparsity of the contour values.